The Effect of Isotonic Saline Nasal Lavages in Improving Symptoms in SARS-CoV-2 Infection: A Case-Control Study - Spinato, Giacomo; Fabbris, Cristoforo; Costantini, Giulio; Conte, Federica; Scotton, Pier Giorgio; Cinetto, Francesco; De Siati, Rosalba; Matarazzo, Alessandro; Citterio, Marco; Contro, Giacomo; De Filippis, Cosimo; Agostini, Carlo; et al. (Frontiers in Neurology, 2021)
Background – Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) mainly colonizes nasopharynx. In upper airways acute infections, e.g. the common cold, saline nasal irrigations have a significant efficacy in reducing symptoms. The present study aimed to test the efficacy of nasal lavages in upper airways symptoms of Coronavirus Disease 2019 (COVID-19). Methods – A series of consecutive adult subjects who tested positive for SARS-CoV-2 from December 2020 to February 2021 performed daily nasal lavages with saline solution (Lavonase® – Purling, Lugo di Romagna, Italy) for 12 days, starting on the day after the SARS-CoV-2 positive swab. A control group included a historical series of patients who were infected in February-March 2020 and who did not perform lavages. An ad hoc questionnaire regarding symptoms was administered to each subjects at base-line and ten days after diagnosis (i.e. on the same day of the control swab) in both cases and controls. Results – a total of 140 subjects were enrolled. 68 participants in the treatment group and 72 in the control group were included. 90% of respondents declared the lavages were simple to use and 70% declared they were satisfied. Symptoms of blocked nose, runny nose, or sneezing decreased by an average of 24.7% after the treatment. Blocked nose and sneezing increased in the same period of time in the control group. Ears and eyes symptoms, anosmia/ageusia symptoms, and infection duration (10.53 days in the treatment group and 10.48 days in the control group) didn’t vary significantly among the two groups. Conclusion – Nasal lavages resulted to significantly decrease nasal symptoms in newly diagnosed SARS-CoV-2 patients. These devices proved to be well-tolerated and easy to be used. Further studies on a larger number of subjects are needed in order to possibly confirm these preliminary results.